2021
DOI: 10.1021/acs.jproteome.1c00458
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Modeling of Plasma Metabolic and Lipoprotein Biomarkers of SARS-CoV-2 Infection in Spanish and Australian COVID-19 Patient Cohorts

Abstract: Quantitative plasma lipoprotein and metabolite profiles were measured on an autonomous community of the Basque Country (Spain) cohort consisting of hospitalized COVID-19 patients (n = 72) and a matched control group (n = 75) and a Western Australian (WA) cohort consisting of (n = 17) SARS-CoV-2 positives and (n = 20) healthy controls using 600 MHz 1H nuclear magnetic resonance (NMR) spectroscopy. Spanish samples were measured in two laboratories using one-dimensional (1D) solvent-suppressed and T2-filtered met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 46 publications
6
43
0
Order By: Relevance
“… 53 These data can also be corroborated by the increased level of lactate in the severe symptom group and higher formate levels for the moderate symptom group. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“… 53 These data can also be corroborated by the increased level of lactate in the severe symptom group and higher formate levels for the moderate symptom group. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Masuda et al 64 reported that apolipoprotein A1 and apolipoprotein A2 were reduced during SARS-CoV2 infection, which has previously been associated with a variety of cardiovascular risk factors and mortality from pulmonary hypertension (PHT) and may have mechanistic significance with respect to blood hemodynamic and coagulation changes found in SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 However, the activation of cholesterol biosynthesis is a result of decrease in cellular cholesterol level, and subsequent activation of SREBP-2 is involved in the exocytosis process of SARS-CoV2, which explains its role in virus budding and envelop formation. 62,63 Recently, Masuda et al 64 reported that apolipoprotein A1 and apolipoprotein A2 were reduced during SARS-CoV2 infection, which has previously been associated with a variety of cardiovascular risk factors and mortality from pulmonary hypertension (PHT) and may have mechanistic significance with respect to blood hemodynamic and coagulation changes found in SARS-CoV-2 infections.…”
Section: Lung Ct Diagnosis Using Syngo Dual Energy Lungmentioning
confidence: 99%
“…It is also known that LDL and cholesterol are key mediators of inflammation ( Chróinín et al, 2014 ), which could also have a different extent in recovered and naïve subjects following vaccination. Notably during acute COVID-19 infection, where both lipid bilayer degradation induced by the spike protein and severe inflammation occur, cholesterol and LDL5 are also significantly altered with respect to healthy values, Figure 4 , first column ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ; Ballout et al, 2021 ; Bizkarguenaga et al, 2021 ; Lodge et al, 2021 ; Masuda et al, 2021 ; Meoni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 H nuclear magnetic resonance (NMR) spectroscopy analysis of biofluids produces profiles that show characteristic responses to changes in physiological status and has been used in a few studies in the past to monitor changes in urinary metabolite levels in mice administered different types of influenza vaccines ( Sasaki et al, 2019 ) or to identify serum markers predictive of adverse reactions against smallpox ( McClenathan et al, 2017 ) as well as metabolic signatures of responses induced by a series of commonly used human vaccines, as reviewed in ( Diray-Arce et al, 2020 ). On the other hand, 1 H NMR has been also successfully used to monitor changes in metabolites and lipoproteins induced by SARS-CoV-2 infection ( Bruzzone et al, 2020 ; Kimhofer et al, 2020 ; Ballout et al, 2021 ; Baranovicova et al, 2021 ; Bizkarguenaga et al, 2021 ; Julkunen et al, 2021 ; Lodge et al, 2021 ; Masuda et al, 2021 ; Meoni et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%